The work of nun Joanna (Reitlinger) in the context of archpriest Sergius Bulgakov’s “christosophy” concept (on the example of the paintings of the Church of St. John the Warrior in Medon and the Chapel of St. Basil the Great in London) - Patrusheva Maria B. (Vestnik Svâto-Filaretovskogo instituta, 2023)
The article is dedicated to the analysis of the paintings of the church of St. John the Warrior in Medon, created by Y. N. Reitlinger, later nun Joanna, in 1931–1932, and the chapel (of the church) of St. Basil the Great of the ecumenical Commonwealth of St. Albans and St. Sergius of Radonezh in London in 1945–1947. The theology and iconography of nun Joanna were shaped and developed in line with the theology (sophiology) of archpriest Sergius Bulgakov. The epistolary legacy of nun Joanna is not extensive, but it is possible to trace a dialogue between artist and theologian about the meaning of creativity and the significance of tradition for art and icon painting. The strict architectural restrictions, on the one hand, were an obstacle in the work of nun Joanna, but, on the other hand, they contributed to the development of a holistic original solution and the emergence of new iconography, both of individual subjects in the church of St. John the Warrior and of the entire painting in the chapel of St. Basil the Great. The compositional and icon-painting sources of the paintings of the church in Medon were recorded by the artist, as well as a note by archpriest Sergius Bulgakov with his vision of the painting plan. One can estimate to what extent Y. N. Reitlinger followed the recommendations of Fr. Sergius and whether her work was a development of this plan. The programme of the painting of the chapel of St. Basil the Great was commented on by nun Joanna from the narrative side, but with regard to the pictorial and iconographic sources, we can only make assumptions, viewing this painting as a theological development of the themes of the Second Coming of Christ and the history of the Church as the history of salvation, which started in the Church in Madon.